Synthesis Of Mesoporiic Silica From Rice Husk Ash For Pinostrobin Based Drug Delivery - Rifia Wulandari; Saprini Hamdiani; Nurul Ismillayli (Acta Chimica Asiana, 2019)
A study has been conducted on the synthesis of mesoporous silica as introductory material pinostrobin anticancer compounds. The aim of this study was to synthesis paramagnetic mesoporous silica from rice husk ash waste; knowing the characteristics of silica gel and mesoporous silica from rice husk and the value of adsorption capacity (Q). Based on the results of the study, it was found that mesoporous silica can be synthesized from the rice husk ash waste. Characterization using FTIR produces silanol (Si-OH), and siloxan (Si-O-Si). The use of 30% w/w tartaric acid as a template doesn’t change the functional groups of silica. The optimum conditions of adsorption of pinostrobin compounds by mesoporous silica at the adsorption capacity of 7.049 mg/g. In simulated intestinal fluids (pH 7.4),pinostrobin is released slowly at every hour, then slightly increases at the 10th hour and continues to increase again slowly so that the pinostrobin compound is completely released at 12 hours.